USING MODERN TECHNOLOGIES TO IMPROVE SPEAKING SKILLS (Лучшие интеллектуальные исследования, 2025)
Abstract: In recent years, the integration of modern technologies in language learning has revolutionized the way speaking skills are developed and honed. This article explores the various technological tools and platforms that enhance oral proficiency in foreign languages. It delves into the benefits of using virtual classrooms, language learning apps, speech recognition software, and social media, highlighting their impact on fluency, pronunciation, and confidence. By leveraging these technologies, educators and learners can create immersive and interactive environments that facilitate effective speaking practice. The article also addresses potential challenges and offers practical recommendations for maximizing the use of technology in language instruction.